Juridical Review of Conduct of Traffic Violations Based on Lei No.6/2003 - Martins Freitas, Raimundo; Monteiro, Seguito; Gusmão, Eugenio de Sousa (IHSA Institute, 2024)
Highway traffic plays a crucial role in transportation, but it requires further development to ensure it covers all areas and integrates seamlessly with other modes of transport. Unfortunately, the condition of roads and pedestrian facilities falls below standard, leading to frequent accidents due to lack of traffic awareness among drivers and pedestrians. The Codigo Estrada government regulation in Timor Leste emphasizes the importance of road safety and transportation, outlining rules for vehicles and pedestrians. To gather data for this study, the authors relied on empirical laws and interviews. Traffic violations that result in accidents are met with criminal and administrative sanctions, aiming to prevent future incidents. Hence, it is essential for the government to implement annual plans and educate the public through mass media to enhance awareness of traffic regulations in Timor Leste